Temporal trends of climatic variables and water footprint of rice and wheat production in Punjab, India from 1986 to 2017 - Durba Kashyap (IWA Publishing, 2021)
The agriculture sector is vulnerable to climate change and related changes in the hydrological cycle. In order to understand the changes in climatic variables and their implications for agricultural water consumption, the present study aims to analyse the temporal variability of climatic factors and water footprint (WF) of rice and wheat during the period 1986–2017 in Ludhiana, Punjab. Further, it aims to identify the dominant climatic factors that cause variation in reference evapotranspiration (ETo) and WF of rice and wheat. WF was estimated using CROPWAT, and Path analysis was used to determine the dominant climate variables. Temporal trends of climate variables were analysed using the Mann–Kendall test. The total WF of both rice and wheat shows a significant declining trend over the past 32 years. Sunshine duration and wind speed were the dominant factors influencing the variability of total WF of rice and wheat, respectively, whereas rainfall strongly influenced the green and blue WF of rice and wheat. Rainfall had a high variability, and consequently, irrigation water requirement was highly fluctuating. This indicates the significant impact of present and projected erratic pattern of precipitation on agriculture due to climate change and reiterates the importance of adaptive measures like rainwater harvesting and capacity building. HIGHLIGHTS Influence of climate variables on WF of rice and wheat was analysed for the first time for India.; Rainfall significantly influenced both green and blue WF of rice and wheat.; High variability in rainfall and irrigation water requirement highlights the urgent need for green water management.; Assessment of long-term trends in climate and WF is crucial for strategizing cropping patterns.; The study confirms the existence of ‘evaporation paradox’ and ‘solar dimming’ in Punjab, India.;